Betriebliche Determinanten der Beschäftigung älterer Arbeitnehmer - Bernhard Boockmann; Thomas Zwick (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2004)
– The labour force participation of older workers in Germany is low compared with other countries. A decisive factor in this respect is not least the employment decisions made by companies. This paper shows which company characteristics lead to a higher or a lower employment share of older workers. It becomes clear that factors which prevent firms from adapting their age structure lead to a greater proportion of older workers. In particular the role of the works council is important in this respect. Conversely, firms with a relatively large number of trainees, a large proportion of women in the workforce and modern technical equipment employ relatively few older workers. Finally the estimation of those responsible for personnel issues regarding older workers plays a role in explaining the employment share of older workers only in smaller firms with fewer than 100 employees. This indicates that those responsible for personnel issues in larger firms are only able to adapt the age structure to their estimations to a small extent.
Keywords: 330; ältere Arbeitnehmer; Erwerbsbeteiligung; Arbeitskräftenachfrage - Determinanten; Personalpolitik; Arbeitgeber - Einstellungen; IAB-Betriebspanel